New chronological research of the late Bronze Age in Scandinavia - Kneisel, Jutta (Danish Journal of Archaeology, 2013)
The concept of time dominating in archaeological science differs widely from that of prehistoric cultures. Still, ‘time’ is one of the most important criteria for the reception of cultural and historical processes. Compartmentalising time creates artificial breaches, used as methodical means of breaking down the continuum. This article analyses the currently valid chronological concept for the late Nordic Bronze Age created by Evert Baudou with the objective of finding possible toeholds for further subdivisions. Baudou’s generous conception of the time periods IV–V makes the realisation of chronological adjustments very difficult. Using Baudou’s catalogue of Danish grave finds, the author tries to further subdivide these time-horizons with the help of a correspondence analysis. By making use of several intermediate steps, it is possible to discern two more temporal subdivisions within the devolution of periods IV–V. The existence of these four phases is supported by 14C-dates.